Analisis Mengenai Diskresi dengan Freies Ermessen - Lathifah, Hilma; Frinaldi, Aldri (Lembaga Yasin AlSys, 2024)
This discretion has consequences from the concept of a welfare state law, where discretionary authority is a necessity for the state to implement welfare for society effectively and efficiently. Discretion also acts as a substitute or workaround for weaknesses in regulations, enabling governments to respond and handle unforeseen situations in a manner consistent with general principles of good governance. The aim of this research is to investigate and identify effective monitoring and accountability mechanisms for the use of Freies Ermessen in the legal system in order to increase integrity and fairness in decision making. The research method used in this research is a qualitative approach with descriptive methods and literature studies. A qualitative approach was chosen because it provides the ability to deepen and understand complex phenomena and allows researchers to explore various perspectives and relevant contexts. The research results show that regarding the use of Freies Ermessen in the legal system, there is a need to develop effective monitoring and accountability mechanisms. Transparency in the decision-making process, setting clear standards, and community involvement are key to ensuring that discretion is used with integrity and in accordance with legal principles. In addition, the role of an independent court system in examining decisions taken and strengthening accountability mechanisms for authority holders is essential in preventing abuse of power.